DISCRETE-TIME CONTROL OF LINEAR MULTIVARIABLE SYSTEMS WITH EITHER SINGULAR OR ILL-CONDITIONED TRANSFER FUNCTION MATRICES - Azarskov, Valerij; Zhiteckii, Leonid; Solovchuk, Klavdiia (Proceedings of National Aviation University (archive), 2014)
The control of multivariable linear discrete-time, time-invariant systems whose transfer function matrices are either singular or ill-conditioned is considered. It is assumed that there are arbitrary unmeasurable but bounded disturbances, and the parameters of these systems may be somewhat unknown. The optimal controller is derived by using the pseudoinverse of the system transfer function matrix. The boundedness of all signals caused by this controller and also the robustness properties of the controller in the presence of parameter uncertainty are proved. Numerical examples are given to support the theoretical investigations.